Nanosized carriers based on amphiphilic poly-N-vinyl-2-pyrrolidone for intranuclear drug delivery. (4th May 2018) - Luss, Anna L; Kulikov, Pavel P; Romme, Sven B; Andersen, Camilla L; Pennisi, Cristian P; Docea, Anca O; Kuskov, Andrey N; Velonia, Kelly; Mezhuev, Yaroslav O; Shtilman, Mikhail I; Tsatsakis, Aristidis M; Gurevich, Leonid
Aim: Ability to deliver drugs into the cell nuclei can significantly increase the efficacy of cancer therapies, in particular in the case of multidrug-resistant cancerResults: Polymer nanocarriers based on amphiphilic thiooctadecyl-terminated poly-N-vinyl-2-pyrrolidone were produced and loaded with a model hydrophobic drug,  curcumin. Two commonly used loading approaches – emulsification and ultrasonic dispersion – were found to lead to two different size distributions with distinctively different biological effect. While nanocarriers produced via the emulsion method penetrated cells by dynamin-dependent endocytic mechanisms, sub-100 nm dispersion-produced nanocarriers were capable of crossing the membranes via biologically independent mechanisms.Conclusion: This finding opens an intriguing possibility of intranuclear delivery by merely tailoring the size of polymeric carriers, thus promising a new approach for cancer therapies.